Metabolic Reprogramming in CD8+ T Cells During Acute Viral Infections - Gupta, Shubhranshu S.; Wang, Jin; Chen, Min (Frontiers in Immunology, 2020)
CD8+ T cells represent one of the most versatile immune cells critical for clearing away viral infections. Due to their important role, CD8+ T cell activation and memory formation during viral infection have been the focus of several studies recently. Although CD8+ T cell activation and memory formation have been associated with metabolic alterations, the molecular understanding behind T cells choosing one type of metabolism over others based on their differentiation stage is still unclear. This review focuses on how the signaling molecules and cellular processes that are characteristic of CD8+ T cell activation and memory formation also play a critical role in selecting the specific type of metabolism during viral infections. In addition, we will summarize the epigenetic factors regulating these metabolic alterations.